Historical Jesus research and relevance in South Africa - Botha, Pieter J. J. (HTS teologiese studies, 2009)
A brief review of significant developments in South African historical Jesus research during the past three decades is given. Although historical Jesus investigations are not characteristic or even dominant in South African New Testament scholarship, some of the achievements of the scholars working in this field are not only significant contributions to the discipline but are also of considerable relevance to the challenges facing biblical scholarship in general in the South African context. South African historical Jesus publications show a distinct development from the almost unproblematic application of Jesus’ words and actions at the earlier stage to a sophisticated and nuanced juxtaposing and interrelating of modern and ancient settings at the present time. It is suggested that these developments can contribute to the exploration of alternative and appropriate theological discourses.